SUSTAINABILITY: MYTH OR REALITY? Understanding the Concept and Nature of Sustainability and the Factors Affecting It - Deriquito, Lea C. (Philippine Journal of Social Development; Vol 1 (2009): Philippine Journal of Social Development, 2011)
The study analyzes two sustainability frameworks and centers on community-based and people-oriented development projects, focusing on the perceptions, specific circumstances and experiences of different stakeholders involved in these projects.   The significant outcome of the study is the conceptualization of a more comprehensive and unified definition of sustainability and a rating scale for evaluating and monitoring development projects’ progress towards sustainability.